تحاكم البنوك الإسلامية في قضاياها لدى القوانين الوضعية: دراسة فقهية قانونية - بركات، عماد نهاد أحمد (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2017)
This study containts of a compartive search for issue of arbitration and branched for several juris razed rules and ideological issues, in order to show problem arbitration of Islamic banks in the civil courts within Islamic lawful solutions which we able to apply Islamic Sharia'a (law) in those judgment. The researcher has compared among schooler's views in jurispadental issues. He has indicated the preponderant view in issue, or he has tipped to views in Islamic heritage, books, modern researches which he has checked. The researcher used the analytical approach to know why didn't apply Sharea'a. Do it apply on banks issue? Also to know what was the reason to not apply Islamic Share'a (laws) in the previous Islamic issues? The researcher has concluded that the best solution for Islamic banks to build up international Islamic economic court which applies Sharea'a. He said that pleading to remove injustice using civil laws in necessity through Islamic limits, hence he mentioned that the contract has to contain strategies and procedures which are used until the court will be built up. He summarized the importance of legalizing of handlings, he suggested standards for them to rationalize treat with them internationally in civil courts.